2006
DOI: 10.2298/vsp0609819d
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of chronic hepatitis C in relation to virus genotype

Abstract: The present data support the hypothesis that distinct genotypes of HCV are associated with the particular histopathological manifestation of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Regarding the association between the number of α-SMA HSCs and the grade of necro-inflammation, our study did not find any statistically significant correlation between these two variables, which is in accordance to results reported by other published papers [33,76,78,80,93,94]. This aspect could be explained by the fact that HSCs were already activated by HCV, even in the absence of severe necro-inflammatory activity [75,80,99].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the association between the number of α-SMA HSCs and the grade of necro-inflammation, our study did not find any statistically significant correlation between these two variables, which is in accordance to results reported by other published papers [33,76,78,80,93,94]. This aspect could be explained by the fact that HSCs were already activated by HCV, even in the absence of severe necro-inflammatory activity [75,80,99].…”
Section: Discussionsupporting
confidence: 91%
“…The dominance of genotype 3 is consistent with the pattern of HCV genotypes distribution among risk groups in Western Europe, as in Serbia [12][13][14] . A recent study conducted in Serbia confirmed that the patients infected with HCV genotype 1b had more frequently moderate or severe necroinflammatory activity of the disease, and a significantly higher grading score as compared with other genotypes 16 . A recent study conducted in Serbia confirmed that the patients infected with HCV genotype 1b had more frequently moderate or severe necroinflammatory activity of the disease, and a significantly higher grading score as compared with other genotypes 16 .…”
Section: Discussionmentioning
confidence: 99%